Sigambra sundarbanensis sp. nov. (Annelida, Pilargidae) from the Indian sector of Sundarbans Estuarine System, with remarks on parapodial glands - Bhowmik, Moumita; Ghoshal, Priya; Salazar-Vallejo, Sergio I.; Mandal, Sumit (European Journal of Taxonomy, 2021)
A new pilargid species, Sigambra sundarbanensis sp. nov., is described from the rivers Matla and Thakuran, in the central Indian sector of the Sundarbans Estuarine System. This species is characterized by several characters such as the starting position of the notopodial hooks, the length of the median antenna and the variation in number of the neuropodial chaetae. These characters distinguish the new species from its congeners. Some parapodial glands have been found in individuals of this species. The new species closely resembles Sigambra parva (Day, 1963). Additionally, an updated key of genus Sigambra is provided, along with a table indicating their morphological variations and a global map showing their type localities.